The effect of probiotic fermented milk and inulin on the functions and microecology of the intestine - Sairanen, Ulla; Piirainen, Laura; Gråsten, Soile; Tompuri, Tuomo; Mättö, Jaana; Saarela, Maria; Korpela, Riitta (Journal of dairy research, 2007)
We investigated the effects of a probiotic fermented milk and inulin on gastrointestinal function and microecology. The study was double-blinded and comprised 66 healthy adults (22 male, 44 female), mean age 40 years (range, 22–60 years). After a 12-d baseline period the subjects were randomized to consume, for 3 weeks, 3×200 ml daily of either (1) a fermented milk with probiotics (Bifidobacterium longum BB536, Bifidobacterium spp. 420 and Lactobacillus acidophilus 145), (2) a fermented milk with the same probiotics plus 4 g inulin, or (3) a control fermented milk. During the last 7 d of the baseline and the intervention periods, the subjects kept a record of their defaecation frequency and gastrointestinal symptoms, and collected all their faeces. Intestinal transit time, stool weight and faecal enzyme activities were measured. Thirty-nine subjects were randomized to give faecal samples for analysis of pH and microbes, including lactobacilli, bifidobacteria, coliforms, Escherichia coli, Bacteroides and Clostridium perfringens. Consumption of fermented milk with probiotics or with probiotics and inulin increased the faecal number of lactobacilli (P=0·009, P=0·003) and bifidobacteria (P=0·046, P=0·038) compared with the baseline. Compared with the control fermented milk, both active products increased lactobacilli (P=0·005, ANCOVA). Subjects consuming fermented milk with probiotics and inulin suffered from gastrointestinal symptoms, especially flatulence, more than the others (P<0·001). In conclusion, the probiotic fermented milk product had a positive effect by increasing the number of lactobacilli and bifidobacteria in the colon. Inulin did not alter this effect but it increased gastrointestinal symptoms.